Enzymatic Hydrolysis Of Native Granular And Modified Starch Below Gelatinization Temperature - Yussof, Nor Shariffa (2010)
The effects of mild heat treatment, cross-linking and annealing towards the susceptibility of granular starch to enzymatic hydrolysis at sub-gelatinization temperature (35ºC) were investigated. Mild heat-treatment was carried out at 60ºC for 30 minutes. Cross-linking was performed by re-acting the starches with 1% epichlorohydrin (ECH), while for annealing the starches were annealed at 50ºC for 72 hours. Tapioca and sweet potato starches were subjected to enzymatic hydrolysis with a mixture of fungal α-amylase and glucoamylase at 35°C for 24 hours. The dextrose equivalent (DE) value of heat-treated starch increased significantly compared to native starch i.e. 36% to 50% and 27% to 34% for tapioca and sweet potato starch, respectively. The DE of cross-linked tapioca starch decreased significantly from 36% to 28%. Both annealed tapioca and sweet potato starches were hydrolyzed to a greater degree compared to native starch. Scanning Electron Microscopy (SEM) examination on hydrolyzed starches showed that enzymatic erosion occurred mainly at the surface of starch granules. Hydrolyzed heat-treated starch exhibited rougher surface and porous granules compared to native starch. SEM micrograph revealed that hydrolyzed cross-linked starches had less porous granules as compared to their native counterparts. Both hydrolyzed annealed starches had more porous granules and rougher surface as compared to native starch due to enzymatic erosion.